Relationship of Parieto-Occipital Brain Energy Phosphate Metabolism and Cognition Using 31P MRS at 7-Tesla in Amnestic Mild Cognitive Impairment - Das, Namrata; Ren, Jimin; Spence, Jeffrey S.; Rackley, Audette; Chapman, Sandra B. (Frontiers in Aging Neuroscience, 2020)
Background: Neuroenergetics, a study of brain energy metabolism (BEM), may uncover cues for early disease biomarkers that potentially trigger downstream neuropathological changes in amnestic mild cognitive impairment (aMCI), a transitory stage of Alzheimer’s disease (AD). Advancements in brain imaging modalities, such as in vivo 31phosphorus magnetic resonance spectroscopy (31P MRS) at higher magnetic strength, offer promising platforms to measure energy and membrane phospholipid metabolites, a window to understand BEM. The primary goal was to quantify distinct features of phosphorus metabolites in parieto-occipital lobes using 31P MRS at 7Tesla in aMCI. Another objective was to examine the clinical significance of the metabolites to brain-behavior relationships. Specifically, we examined the correspondence across BEM and membrane phospholipid indices in parieto-occipital regions of the brain with cognitive performance- executive functions (EF), memory, attention, and visuospatial skills. Methods: 19 aMCI participants enrolled in the study. Each participant completed a cognitive assessment and a scan using partial volume-coil 31P MRS over parieto-occipital lobes at 7Tesla. BEM indices were measured using three energy indicators: energy reserve (PCr/t-ATP), energy consumption (intracellular_Pi/t-ATP), and metabolic state (PCr/intracellular_Pi) along with regulatory co-factors of BEM-intracellular Mg2+ and pH; whereas the ratio of phosphomonoesters (PMEs) to phosphodiesters (PDEs) represented membrane phospholipid indicator. Results: 31P MRS data over parieto-occipital lobes showed thirteen well-resolved peaks of the energy and membrane phospholipid metabolites at 7Tesla. The higher BEM indices were associated with lower cognitive performance of memory [(energy reserve indicator: CVLT p=0.004), (metabolic state indicator: CVLT p=0.007)], executive function [(metabolic state indicator: TOSL (p=0.044)], and attention [(pH: selective auditory task, p=0.044)]. The finding of higher brain energy indices in the parieto-occipital lobes associated with lower cognition may represent compensatory hypermetabolism during the early stages of brain disturbances in aMCI. Conclusion: The critical contribution of this work was to develop and test a methodology to quantify neurometabolic markers of energy and membrane phospholipid metabolites at 7Tesla in aMCI. Additionally, the study findings implicated the role of BEM as an early neurometabolic marker of brain changes linked to cognitive decline in the preclinical stages of AD.